2015
DOI: 10.1186/s12889-015-2387-9
|View full text |Cite
|
Sign up to set email alerts
|

A gloomy picture: a meta-analysis of randomized controlled trials reveals disappointing effectiveness of programs aiming at preventing child maltreatment

Abstract: BackgroundConsistent findings about the effectiveness of parent programs to prevent or reduce child maltreatment are lacking.MethodsIn the present meta-analysis we synthesized findings from 27 independent samples from randomized controlled trials (RCTs) on the effectiveness of 20 different intervention programs aimed at (i) preventing the occurrence of child maltreatment in the general population or with at-risk but non-maltreating families, or (ii) reducing the incidence of child maltreatment in maltreating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 62 publications
4
119
2
1
Order By: Relevance
“…Similarly, it is notable that Loman and Siegel (2012) document substantial effects on family safety even a decade after an anti-poverty service, provided to families as part of involvement with social services, which assured that the family had reliable funds for food, clothing, and housing. However, meta-analytic data suggest that in order to be reliably successful in preventing child maltreatment, interventions may have to include parent training, and not just support (Euser, Alink, Stoltenborgh, Bakermans-Kranenburg, & van IJzendoorn, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is notable that Loman and Siegel (2012) document substantial effects on family safety even a decade after an anti-poverty service, provided to families as part of involvement with social services, which assured that the family had reliable funds for food, clothing, and housing. However, meta-analytic data suggest that in order to be reliably successful in preventing child maltreatment, interventions may have to include parent training, and not just support (Euser, Alink, Stoltenborgh, Bakermans-Kranenburg, & van IJzendoorn, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Parent programs aimed at preventing or reducing child maltreatment have grown over the last several decades, with findings from a recent meta-analysis demonstrating the importance of the intervention’s focus on “training” versus “support” (Euser, Alink, Stoltenborgh, Bakersman-Kraneburg, & van Ijzendoorn, 2015), especially with the highest risk families (those where maltreatment has occurred). However, data for how well parenting training and/or support programs work with fathers is limited at best (Lee et al, 2013; Osborne et al, 2016; Scourfield, 2014;).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of a recent meta-analytic review concluded that the evidence MATERNAL CORPORAL PUNISHMENT 7 of the effectiveness of preventive interventions for child maltreatment paints a gloomy picture (Euser, Alink, Stoltenborgh, Bakermans-Kranenburg, & van IJzendoorn, 2015). Universal prevention programs aside, existing interventions that prevent early CPUN are typically offered to parents based on risk factors measured at a single point in time (e.g., Zielinski, Eckenrode, & Olds, 2009).…”
Section: Introductionmentioning
confidence: 99%